CASH WAQF LINK SUKUK COLLECTION: EXPLORING INTENTIONS, OBSTACLES, SOLUTIONS, AND STRATEGIES FOR INSTITUTIONAL WAQIFS - Arianty, Erny; Yustiani, Syanni; Haniyah, Rizqi; Balative, Iqbal (Akurasi : Jurnal Studi Akuntansi dan Keuangan, 2024)
The low intensity of the waqf community means that waqf collection through Cash Waqf Linked Sukuk (CWLS) has not reached the expected potential. This causes many planned social programs to be delayed. This research aims to explore the intensity, problems, solutions, and strategies for collecting CWLS, as well as determining and ranking each cluster and its elements. The method used is a qualitative method with the Analytical Network Process (ANP) approach. Research informants from BWI, KNEKS, Sharia Bank, BPKH, Nazir, and the government. This research found four aspects that influence the decision to invest in CWLS and related problems. The knowledge aspect is most influenced by low understanding and literacy, the conformity aspect by complex and non-standard accounting treatment, the environmental aspect by ineffective CWLS management services, and the behavioral aspect by the negative views of fund owners. The highest influence for cluster solutions on intensity is the socialization element. The most important strategy chosen is the CSR leverage channel strategy in BUMN or government institutions for placement in CWLS.